Impact of switching prophylaxis treatment from factor VIII to emicizumab in hemophilia A patients without inhibitors. (31st December 2023) - Escobar, Miguel; Agrawal, Neha; Chatterjee, Sagnik; Bhattacharya, Swastik; Caicedo, Jorge; Bullano, Michael; Schultz, Bob G.
Abstract: Background: Factor VIII (FVIII) replacement and emicizumab are effective at preventing bleeds in patients with hemophilia A (HA). Though benefits of emicizumab among inhibitor patients with HA (PwHA) are well established, more real-world evidence among non-inhibitor patients is needed. Methods: Using a United States healthcare claims database, we compared billed annualized bleed rates (ABRb ) and the total cost of care (TCC) before and after switching from FVIII prophylaxis to emicizumab among non-inhibitor male PwHA. Bayesian inferences were used to assess the difference in ABRb and TCC per patient per year (PPPY) pre- versus post-prophylaxis switch. Results: We included 101 non-inhibitor male PwHA aged between 3 and 63 years old who switched from FVIII prophylaxis to emicizumab prophylaxis in 2018 or 2019. The ABRb increased from 0.52 to 0.62 ( p  = 0.83) after switch. The posterior probability of the mean ABRb increasing after the switch was 75.54%. The TCC PPPY increased from $517, 143 to $627, 005 ( p  < 0.0001) after switch and the posterior probability of mean costs increasing after the switch was 99.80%. Conclusions: Personalization of care through the identification of the most appropriate therapy for each patient can optimize clinical and economic outcomes. Future real-world evidence research could help establish the value of prophylactic options in targeted populations such as the non-inhibitor male PwHA.